Assessing the Assessors: Language Assessment Knowledge and Beliefs in Thai Preservice English Teachers - Ketkumbonk, Atthasit; Sukying, Apisak (International Journal of Learning, Teaching and Educational Research, 2024)
This study investigates the evolution of language assessment knowledge (LAK) and language assessment (LA) beliefs among 54 Thai preservice English teachers from a public university in northeastern Thailand during their teaching practicum. The participants were selected using convenience sampling. While language assessment literacy (LAL) remains a developing area with varied levels across different contexts, this research addresses the gap by examining changes in LAK and beliefs over time. Using parallel LAK tests and a detailed LA beliefs questionnaire based on Taylor’s (2013) framework, assessments were conducted at the beginning (T1) and end (T2) of the semester. Data were analyzed using descriptive and inferential statistics. The findings revealed a slight improvement in LAK, with mean scores increasing from 31.3 (56.9%) at T1 to 33.19 (60.34%) at T2, indicating a medium level of LAL, though the change was not statistically significant. Despite the modest improvement in technical skills, there was a notable decline in applying local assessment practices. However, the preservice English teachers consistently rated the importance of language assessment highly, with a significant growth in their personal beliefs and attitudes. The study also identified a small but statistically significant correlation between LAK and LA beliefs, highlighting the context-bound nature of assessment practices. These findings highlight the need for context-sensitive training in teacher education programs to better prepare preservice teachers for real-world challenges, emphasizing the importance of integrating theoretical knowledge with practical applications. Further research is recommended to explore these dynamics over a longer period and across diverse educational settings.